Krąg rodzinny prymasa Andrzeja Olszowskiego: Family circle of primate Andrzej Olszowski - Sławiński, Tomasz (Prace Polonistyczne, 2019)
The article contains an analysis of family and genealogical connections of one of the most prominent historical figures of the Polish-Lithuanian Commonwealth in the 17th century – Andrzej Olszowski, Archbishop of Gniezno and Primate of Poland – politician, clergyman, writer and intellectual. He was a descendant of a middle-class gentry who settled in the land of Łęczyca, sealing himself with the Wilczekosy (Wolf Scythes) coat of arms, attesting to the origin of Clan Prusy (the medieval refugees from Pruthenia attacked by Theutonic Order). Despite this modest pedegree he had such outstanding figures among his ancestors as Andrzej Frycz Modrzewski – a Renaissance writer and humanist, and his nepoties included the famous brothers Załuscy – bishops, patrons of art and science, the creators of the library, which became the leaven of the polish National Library.